Chromosome-scale reference genome assembly of a diploid potato clone derived from an elite variety. Issue 12 (17th September 2021) - Freire, Ruth; Weisweiler, Marius; Guerreiro, Ricardo; Baig, Nadia; Hüttel, Bruno; Obeng-Hinneh, Evelyn; Renner, Juliane; Hartje, Stefanie; Muders, Katja; Truberg, Bernd; Rosen, Arne; Prigge, Vanessa; et al.
Abstract: Potato ( Solanum tuberosum L.) is one of the most important crops with a worldwide production of 370 million metric tons. The objectives of this study were (1) to create a high-quality consensus sequence across the two haplotypes of a diploid clone derived from a tetraploid elite variety and assess the sequence divergence from the available potato genome assemblies, as well as among the two haplotypes; (2) to evaluate the new assembly's usefulness for various genomic methods; and (3) to assess the performance of phasing in diploid and tetraploid clones, using linked-read sequencing technology. We used PacBio long reads coupled with 10x Genomics reads and proximity ligation scaffolding to create the dAg1_v1.0 reference genome sequence. With a final assembly size of 812 Mb, where 750 Mb are anchored to 12 chromosomes, our assembly is larger than other available potato reference sequences and high proportions of properly paired reads were observed for clones unrelated by pedigree to dAg1. Comparisons of the new dAg1_v1.0 sequence to other potato genome sequences point out the high divergence between the different potato varieties and illustrate the potential of using dAg1_v1.0 sequence in breeding applications.